360 Degree Feedback Appraisals- An Innovative Approach of Performance Management System (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
360-degree feedback systems are typically introduced as part of individual or organisational development activities. However, 360-degree feedback is increasingly used as an integral part of performance appraisal, relating to administrative decisions such as promotions, terminations and pay (Fletcher & Baldry, 1999; Fletcher, 2001). There has been vigorous debate among practitioners and academics concerning the role of 360-degree feedback in the HR function (Bracken et al., 1997; Garavan et al., 1997; Handley, 2001). The use of such systems for developmental purposes only is based on the argument that their application for other uses (e.g. linking them to pay or performance appraisal) lessens the impact and outcome from the process (Alimo-Metcalfe, 1998). The concept of 360 degree feedback makes a lot of sense and, if used well, should have a great deal to offer.  It seems to suit the move towards the less hierarchical, more flexibly-structured and knowledge based organisations of the future Professor Clive Fletcher Goldsmiths College, University of London, in today changing and volatile world organisations are continually looking for ways to improve performance, and satisfy the demands of all stakeholders. Achieving this almost inevitably involves change, which then becomes the pivotal dynamic for success.